Illustrated dictionary of cargo handling - Brodie, Peter R. 1947- (Lloyd's of London Press, 2016)
This book gives readers a visual representation of all elements of maritime transport which relate to the handling and movement of cargo. This is particularly for the benefit of shore-based personnel who often do not get the opportunity to see first-hand how the cargoes they are working on are handled and moved. The book covers: Ship types and the parts of ships relating to the handling and stowage of cargo